Bayesian meta-analysis of inter-phenotypic differences in human serum paraoxonase-1 activity for chemical risk assessment. (May 2020) - Darney, K.; Kasteel, E.E.J.; Buratti, F.M.; Turco, L.; Vichi, S.; Béchaux, C.; Roudot, A.C.; Kramer, N.I.; Testai, E.; Dorne, J.L.C.M.; Di Consiglio, E.; Lautz, L.S.
Highlights: Extensive literature search of PON1 genotypic frequencies and activities in humans. Bayesian meta-analysis to quantify inter-phenotypic and inter-individual differences. Specific genotypes showed an exceedance of the 3.16 toxicokinetic uncertainty factors. UFs were below 3.16 when combining genotypic frequencies and activity distributions. Quantitative differences in PON1 polymorphisms are important for chemical risk assessment. Abstract: Human variability in paraoxonase-1 (PON1) activities is driven by genetic polymorphisms that affect the internal dose of active oxons of organophosphorus (OP) insecticides. Here, an extensive literature search has been performed to collect human genotypic frequencies (i.e. L55M, Q192R, and C-108T) in subgroups from a range of geographical ancestry and PON1 activities in three probe substrates (paraoxon, diazoxon and phenyl acetate). Bayesian meta -analyses were performed to estimate variability distributions for PON1 activities and PON1-related uncertainty factors (UFs), while integrating quantifiable sources of inter-study, inter-phenotypic and inter-individual differences. Inter-phenotypic differences were quantified using the population with high PON1 activity as the reference group. Results from the meta -analyses provided PON1 variability distributions and these can be implemented in generic physiologically based kinetic models to develop quantitative in vitro in vivo extrapolation models. PON1-related UFs in the Caucasian population were above the default toxicokinetic UF of 3.16 for two specific genotypes namely −108CC using diazoxon as probe substrate and, −108CT, −108TT, 55MM and 192QQ using paraoxon as probe substrate. However, integration of PON1 genotypic frequencies and activity distributions showed that all UFs were within the default toxicokinetic UF. Quantitative inter-individual differences in PON1 activity are important for chemical risk assessment particularly with regards to the potential sensitivity to organophosphates' toxicity.